KOLABORASI EDUKATIF DALAM PENGAJARAN BAHASA INGGRIS BERBASIS MEDIA VISUAL DI SDN 2 JEHEM - Komang Dian Puspita Candra; I Gusti Ayu Vina Widiadnya Putri; I Komang Sulatra; Putu Devi Maharani; I Gusti Bagus Wahyu Nugraha Putra (Fakultas Bahasa Asing, 2025)
This community service program aims to improve the basic English skills of elementary school students through a visual-based learning method. The teaching was carried out over 16 sessions at SDN 2 Jehem, Bangli, involving 27 students from a combined class of grades 4, 5, and 6. The materials taught included the Alphabet, Vegetables, Introduce Self, Introduce Other, and Parts of the Body. The learning method utilized visual media such as flashcards, posters, PowerPoint presentations, and was supported by songs and educational games. The results of the program showed that visual-based English teaching successfully increased students’ interest in learning English. The success indicators of using visual media demonstrated strong outcomes, with an average test score of 80.2 and a student mastery level of 98.6%. Students showed high enthusiasm when learning the topics of Alphabet, Fruits and Vegetables, and Parts of the Body.